PENGUJIAN SISTEM PEMBANGKIT LISTRIK TENAGA SURYA SOLAR CELL KAPASITAS 50WP - Junial Heri (Engineering : Jurnal Bidang Teknik, 2012)
An electric voltage can be generated when a beam of sunlight which leads to a elektoda-electrode electrolytesolution.  Less  is more  so  who  ever wrote  Edmund  Becquerel  in 1839, research  continues  to  exert  a solid object  inthe light  of the sun, called  selenium  and  until  the  cells  potovoltaik  (fhotovoltaic)  with  selenium  and  courprousmaterial,  up to  the experts  succeeded in  creating a  photoelectric  measuring devices.  In 1954  the photovoltaic  effectis developed  again  into electrical energy that  is now called  fotovoltaic  cells  or  solar  cells.  In principle,  solar  cellsform  conductive  power  semiconductor  device  which  can  directly  convert solar energy into  electrical  energy  in an efficient form of eco-friendly